Experimental Study of H-Shaped Honeycombed Stub Columns with Rectangular Concrete-Filled Steel Tube Flanges Subjected to Axial Load - Jing Ji; Maomao Yang; Zhichao Xu; Liangqin Jiang; Huayu Song (Advances in Civil Engineering)
The behavior of H-shaped honeycombed stub columns with rectangular concrete-filled steel tube flanges (STHCCs) subjected to axial load was investigated experimentally. A total of 16 specimens were studied, and the main parameters varied in the tests included the confinement effect coefficient of the steel tube (ξ), the concrete cubic compressive strength (fcu), the steel web thickness (t2), and the slenderness ratio of specimens (λs). Failure modes, load-displacement curves, load-strain curves of the steel tube flanges and webs, and force mechanisms were obtained by means of axial compression tests. The parameter influences on the axial compression bearing capacity and ductility were then analyzed. The results showed that rudder slip diagonal lines occur on the steel tube outer surface and the concrete-filled steel tube flanges of all specimens exhibit shear failure. Specimen load-displacement curves can be broadly divided into elastic deformation, elastic-plastic deformation, and load descending and residual deformation stages. The specimen axial compression bearing capacity and ductility increase with increasing ξ, and the axial compression bearing capacity increases gradually with increasing fcu, whereas the ductility decreases. The ductility significantly improves with increasing t2, whereas the axial compression bearing capacity increases slightly. The axial compression bearing capacity decreases gradually with increasing λs, whereas the ductility increases. An analytical expression for the STHCC short column axial compression bearing capacity is established by introducing a correction function (w), which has good agreement with experimental results. Finally, several design guidelines are suggested, which can provide a foundation for the popularization and application of this kind of novel composite column in practical engineering projects.